Accuracy of C-reactive protein and a differentiated white cell count in diagnosing tuberculosis - Gideon Ruder; Richard M.N. Carter; Gina Joubert (Southern African Journal of Infectious Diseases, 2023)
Background: Tuberculosis (TB) is treatable with a high cure rate. In South Africa, 70% of pulmonary TB is microbiologically confirmed. Autopsy studies of HIV-positive people found 45.7% undiagnosed TB cases.